An even hover‐reading of Freud: The work of metaphor. (24th June 2016) - Sauvayre, Pascal; Vegas, Monica
Translations of summary: It is posited that the 'elasticity' of Freud's texts evokes an 'evenly hovering' stance in the reader in order to draw out from his writings the multilayered and latent meanings, which often subvert his manifest discourse. This elasticity is exemplified in the metaphor – a central feature of psychoanalytic epistemology. This hypothesis is tested through a close reading of a text that precisely announces itself on the manifest level as a series of straightforward prescriptions, 'Recommendations to Physicians Practicing Psychoanalysis' (1912). And we find that his use of metaphors (culminating in the telephone metaphor) glides into unexpected and surprising (unconscious) spaces, thus mirroring the analytic process that is the subject of Freud's paper. The text proves itself to be as slippery as the psyche it studies, and for which an 'evenly hovering' stance is best suited for both the reader and for the clinician to be receptive to the workings of the metaphor that reveals unique psychoanalytic truths.